(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Dillenia pentagyna Roxb., a deciduous and medium sized tree, is an ethnobotanically important species of several Asian countries including Bangladesh, Srilanka, and India. Various parts of this endangered tree including leaf, bark, root etc. are used in folkloric medicine systems for a very long time. It is locally used in the treatment of pain, wound healing, diabetes, diarrhea and other disease states. Molecular docking is an important technique to validate the exerted pharmacological actions of a plant or specific phytoconstituents by assessing the binding affinity and interaction pattern between small molecules and particular target receptors. Thus, to justify the notable ethnobotanical importances of D. pentagyna, an in silico study was designed employing selected phytochemicals i.e. isorhamnetin, lupeol, quercetin, kaempferol, and betulin isolated from this plant based on previous literature searches. The molecular docking revealed strong binding affinities (-4.8 to -12.9 kcal/mol) with the respective target proteins: 2OYE, 6COX, 4YK5, 5ZHP, and 1A5H. Besides, in accordance with the Lipinski’s rules, all five selected compounds of D. pentagyna showed promising orally active drug-like characteristics. To recapitulate, the present study has been found parallel with the existing ethnobotanical significance of D. pentagyna as the source of pain, fever, thrombosis, and diarrhea management agent. Bangladesh Pharmaceutical Journal 24(2): 125-132, 2021